2010
DOI: 10.12702/1984-7033.v10n02a02
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hybrids of intra and interspecific crosses in Annonaceae by RAPD markers

Abstract: The purpose of this work was to identify hybrids in intraspecific crosses between sugar apple accessions and interspecific crosses between sugar apple and atemoya accessions by using RAPD markers. Four sugar apple accessions were selected: Seedless P 1 , P 2 , P 3 and P 4 and the atemoya cultivar Gefner (G1). In the pre-female phase the flowers were adequately protected and reciprocal crosses were performed. In crosses where the sugar apple accession Seedless P 1 was used as the male parent, the fruits contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The results of this study and of others published by Souza et al (2010) and Lora et al (2011) suggest that for fruit production, the mutant seedless sugar apple depends on the stimulation by natural or artificial pollination.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The results of this study and of others published by Souza et al (2010) and Lora et al (2011) suggest that for fruit production, the mutant seedless sugar apple depends on the stimulation by natural or artificial pollination.…”
Section: Resultssupporting
confidence: 67%
“…Souza et al (2010) also reported the absence of fruit set after selfpollination in seedless sugar apple.…”
Section: Resultsmentioning
confidence: 95%
“…Sequence homology, generated by the amplification of the M 1 , M 2 , M 3 and M 4 accessions, was high, with 79 to 100% similarity to the INO gene transcription factor in A. squamosa (Figure 3). The amplification of the INO gene, from the specific primers for seeded A. squamosa, from the A. cherimola x A. squamosa Gefner and from the F 1 accessions is due to its conservation in these genotypes as reported for Annonaceae (Souza et al, 2010). On the other hand, the absence of amplification in the Brazilian seedless variety indicates the deletion/discontinuation of this gene, as reported for the 'Thai seedless' variety of A. squamosa (Lora et al, 2011).…”
Section: Plant Materials and The Inheritance Of The Seedless Characteristic In A Squamosamentioning
confidence: 63%
“…The similarity between the M , M 2 , M 3 and M 4 sample sequences and those deposited in the GenBank (accession: GU828033.1) for the transcription factor of the INO gene in A. squamosa was high due to the presence of the INO gene and, consequently, of seeds in its fruits (Souza et al, 2010;Varoquaux et al, 2000). Similarity in 100% of the GenBank sequences, added as a standard with one of the sequences sampled, reinforces the hypothesis of INO gene conservation in seeded A. squamosa accessions (M 1 , M 2 , M 3 ) and in the Gefner cultivar of A. cherimola x A. squamosa (Nachtigal et al, 2005) The INO gene was amplified with bands in the accessions of the seeded sugar apple, the atemoya cultivar Gefner and in all progeny of the F 1 population.…”
Section: Plant Materials and The Inheritance Of The Seedless Characteristic In A Squamosamentioning
confidence: 94%
“…Wild-types (fertile) M 1 , M 2 and M 3 and seedless Bs lines were previously described by de Souza et al (2010), and Ts was described by Lora et al (2011). For whole genome sequencing a wild-type sugar apple fruit was purchased from a retail source in the United States, seeds from the fruit were planted, and one plant grown in the UC Davis Conservatory was sampled for sequencing with voucher herbarium samples stored as DAV225058 and DAV225059.…”
Section: Materials and Methods Plant Materialsmentioning
confidence: 99%